Comparison of the Water Appearance Potential Control of Mosquito Screening Aedes Sp.With Prevention of Transmission Risk Dengue Hemorrhagic Fever in Padang City in 2018 - Aidil Onasis; Mukhlis Mukhlis; Eri Barlian (Science and Environmental Journal for Postgraduate, 2018)
The density of the Aedes sp was a risk factor dengue transmission, the higher density of mosquitoes; it is for people to the higher infect. Container potential of Large Dimension sizes could breed that can transmit Dengue Hemorrhagic Fever (DHF). The purpose of this study was to compare the control of Aedes sp. With the Risk Prevention of Dengue Hemorrhagic Fever Transmission This type of research is descriptive, describing the facilities and control functions in Kubu Dalam, Gunung Sarik and Kurao Pagang Sub District in June to December 2018. The population was the entire Water Container used to. 300 houses, to regulate the Breteau based Density Index The results dimensions of the water container of Mosquito breeding, Gunung Sarik 160 containers, the most Large dimension Bak mandi the potential 30.375%, 131 Large-size Container is Bak mandi have larvae Ae. Aegypti is 30.54% in Kubu Dalam and 182 positive containers there are larvae of Ae. aegypti is 35.71% with Potential Breeding was based on Frequency of Control 27%, Kubu Dalam 29% and 32% in Kurao Pagang. The advantage of potential breeding with the most drag control technique in coal containers is 41.82% Breteau Index amounting to 16.875, the highest number in Bak mandi is 50.00% Breteau Index of 22.14 and the most Kurao Pagang in buckets / jars of 43, 07% Potential rate of larvae density of the Breteau Index of 17.58. It is hoped that the community will engage in more activities related to eradicating mosquito nests to reduce the breeding of Aedes sp mosquitoes, maintaining environmental cleanliness such as draining the bath once a week, in order to break the chain of transmission of dengue.